Educación de calidad en Colombia: Del ODS 4 rezagado a la Agenda 2030 incluyente (LACCEI, 2024)
Colombia ranks sixth among 24 countries in the Latin America and Caribbean region in the implementation of the 2030 Agenda. Despite its preferential position in the region, Colombia has not met any of the seventeen SDGs. In this context of Sustainable Development, emphasis is placed on SDG 4 on Quality Education, from which the research question is formulated: What is the level of achievement of SDG 4 in Colombia with respect to the countries of Latin America and the Caribbean? To answer this question, the design of this research was guided by the positivist position and was implemented through the non-experimental method of causal case study. It is evident that between the SDG Index 2019 and 2021, Colombia has maintained a moderate level of progress at a rate above 50% of the expected trend in SDG 4, but below the necessary trajectory for the achievement of SDG 4 in 2030. Therefore, Colombia has a critical lag in SDG 4, with a medium risk of not achieving this SDG by 2030.